Disponibilidade de fósforo em solo cultivado com braquiária em rotação com soja - Almeida, Danilo Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
With crop rotation it is possible to get benefits by cropping some plant sp ecies with great capacity in uptake and also by enhancing the solubility of less labile phosphorus (P) forms, modifying the dynamics of this nutrient in the soil, and thus improving P availability for next crops. The objective of this work was to verify th e possibility of increasing the yield of soybean in rotation with Brachiaria ruziziensis in the off - season compared to no crop rotation , according to P forms distribution in the soil and availability provided by ruzi grass. A field experiment in no - till ha s been performed in Botucatu, SP since 2001. The experiment was evaluated during two crop years (2012/13 and 2013/14). The experimental design was a complete randomized blocks, with split - split plot arrangement. The plots received sources of P applied in t he soil surface (Natural reactive phosphate of Arad – FNA, Triple Superphosphate – SFT, and a control with no P). In the subplots, the treatments were presence and absence of ruzi grass during the off - season. The sub - subplots received levels of P applied e very year in the seed furrow during the sowing of soybean (0, 30, or 60 kg ha - 1 of P 2 O 5 ). Analyzes of soil fertility and P fractionation were made in samples collected after ruzi grass desiccation and before the sowing of soybean, in 2012. Greater availabi lity of P was observed after ruzi grass cultivation, due to cycling of less available P forms, with lowest concentration of P fixed in deep layers of soil, and higher concentration of P labile and moderately labile in the upper soil layers. The ruzi grass crop increased the concentration of organic matter, potassium and magnesium, next to the soil surface. However, the yield of soybean was lower after ruzi grass than after no crop rotation, during the two crop years. A lower concentration of P in leaf analy sis of soybean was verified, even in ...

Com rotação de culturas é possível obter benefícios do cultivo de algumas espécies vegetais com maior habilidade em absorver e solubilizar formas de fósforo (P) pouco lábeis , alterando a dinâmica deste nutriente n o solo, e assim melhorar a disponibilidade do P para cultivos subsequentes. O objetivo desse estudo foi verificar se é possível obter vantagens na produtividade de soja em rotação com Brachiaria ruziziensis com relação à prática de pousio na entressafra , d e acordo com a distribuição das formas de P no solo em função da disponibilização promovida pela braquiária. Foi dad o continuidade a um exp erimento de campo, conduzido sob semeadura direta desde 2001, em Botucatu, SP. O ensaio foi avaliado durante dois ano s safra (2012/13 e 2013/14), e recebeu o delineamento experimental em blocos casualizados, em parcelas sub - subdivididas. As parcelas receberam fontes de P aplicadas a lanço (Fosfato Natural de Arad – FNA, Superfosfato Triplo – SFT, ou uma testemunha sem P) . Nas sub parcelas, os tratamentos foram o cultivo de braquiária ou solo mantido em pousio na entressafra. As sub - subparcelas receberam doses de P aplicadas anualmente no sulco de semeadura da soja (0, 30, ou 60 kg ha - 1 de P 2 O 5 ). Foram feitas análises de fe rtilidade do solo e fracionamento do P em amostras de solo coletadas após a dessecação da braquiária, antes da semeadura da soja, em 2012. Foi observada maior disponibilidade de P após o cultivo de braquiária, em função da ciclagem de formas pouco lábeis d e P, sendo menor a concentração do P fixado em camadas mais profundas do solo, e maior concentração de P lábil e moderadamente lábil nas camadas mais próximas da superfície. O cultivo da braquiária também resultou no aumento do teor de matéria orgânica, po tássio e magnésio, próximo à superfície do solo. Contudo, a produtividade da soja foi menor após a ...
Keywords: Fósforo; Capim-braquiaria; Biodisponibilidade; Rotação de cultivos; Solos - Teor de fosforo; Bioavailability